Effect of Different Soil Moisture Conservation Techniques for Degraded Land Rehabilitation in Geresse District, Gamo Zone, South Ethiopia - Yenealem Gemi Mekuria; Amare Gojjam Geremew; Wudinesh Naba Yaya; Birhanu Wolde Gindi (CV. Literasi Indonesia, 2025)
Worldwide phenomena, land degradation puts people's livelihoods in jeopardy on a larger spatial scale. The research was conducted on degraded land situated in the midland agro-ecologies of Gerese District, within the Gamo Zone of South Ethiopia, for five consecutive years to evaluate moisture-conserving structures for degraded land rehabilitation and assess farmers' perceptions towards moisture conservation techniques. A randomized complete block design was used to arrange the study, and four different treatments were used: bench terrace, stone bund, stone-faced soil bund, and faanyajuu replicated three times. The study area experienced improvements in physical and chemical characteristics of soil following interventions, such as higher soil moisture content (31.46%) and improved soil pH than the untreated site(as a control). On a stone-faced soil bund, there were observations of a 5.34% soil organic matter content, an improved Cation exchange capacity (26 meq/100 g), and a moderate total nitrogen concentration (0.18%). Than other structures throughout the study years. The interventions also promoted species diversity and richness in treated sites with stone-faced soil bunds compared to untreated land. The biomass production of emerging grasses and shrubs, as well as the growth of test trees, was significantly higher in areas with soil and water conservation structures. The study suggests that midland farmers employ stone-faced soil bunds to raise the soil's moisture content, enhance biomass output, and encourage the growth of test trees and grass. As a result, for the purpose of land rehabilitation, all stakeholders involved should practice soil and water conservation.